Analysis of Research Hotspots and Development Trends of Forestry Ecological Culture Industry - Luyu Huang, Yujie Li, Yukun Cao (Forest Chemicals Review, 1970)
As a product of combining ecological civilization thought with cultural industry, forestry ecological culture industry is an emerging cultural industry model with Chinese characteristics, and also a sustainable industry. Using the bibliometric method, we used the study is based on CiteSpace literature analysis software, CNKI database and Web of Science core collection. We used CiteSpace literature analysis software, based on China Knowledge Network (CNKI) database and Web of Science core collection, to systematically review the research literature related to forestry eco-culture industry from 1994 to 2021. Based on objective data and intuitive knowledge mapping visualization, we analyze and summarize the current research hotspots and development trends of forestry eco-culture industry to further improve the forestry eco-culture industry The results show that: China's forestry ecological and cultural industry is the most important industry in the world. The results show that: China's forestry ecological culture industry is at the stage of industrial innovation. The core research contents include the connotation of forest ecotourism, forest ecotourism resource development and management, ecological industrialization, ecological culture, and ecological tourism. The core research contents include forest ecotourism connotation, forest ecotourism resource development and management, ecological industrialization, ecological culture, forestry culture and tourism integration and industrial development.